Sectors in the Czech Republic and International Tax Planning - Jedlička, Vít; Jedlicka, Pavel (Univerzita Hradec Králové, 2019)
Tax planning and its international dimension is effective way for reducing company's tax liability. Methods used within the tax planning have specific assumptions and not every company can achieve significant tax reduction. Tax planning schemes are strongly connected with intangible assets or capital structure. This contribution is focused on the different sectors and their position in the international tax planning. As a method, the cluster analysis has been selected to gain similar sets with similar sector's attributes. Database Albertina is used as a data source and there are selected variables which are related to the international tax planning. Results show that companies from the service sectors use more tax planning than companies from the others. Cluster analyzes report four sectors with higher application of the tax planning: Accommodation, Real Estate, Financial Sector and Electricity and Gas Supply. ICT is another sector which use tax planning more but the conclusions about it cannot be strong because one of the used clustering method does not include it beside above mentioned four sectors.
Sektory v České republice a daňové plánování
Keywords: Tax Planning; Sectors; Czech Companies; Daňové plánování; Sektory; České společnosti